2015 UK software audit of hepatobiliary scintigraphy. Issue 2 (February 2019) - O'Shaughnessy, Emma R.; Murray, Anthony; Taylor, Jonathan C.; Barnfield, Mark; Cullis, James; Cade, Sarah; Kenny, Bob; Carson, Kathryn J.; Towey, David J.; White, Duncan
Abstract : Introduction: This audit investigated hepatobiliary function imaging in UK hospitals, reviewing protocol differences in acquisition and processing parameters and the effect on calculated gallbladder ejection fraction (GBEF). Participants and methods: Two dynamic data sets were available: one continuous dynamic data set, and the other with a 5-min break to administer the fatty stimulus. Participants used a set of 12 anonymized patient data sets most similar to their standard protocol calculating GBEF using their routine method. Results: Fifty-two UK centres responded. Across all centres for all data sets, there was large variability in GBEF quoted, mostly owing to variations in the calculation method, motion correction and imaging type/times. The largest contributor to GBEF variation was time acquired after stimulus which varied from 20 to 70 min. Only 48.1% centres acquired for 60 min after stimulus, which is the acquisition time stated in normal range references. Overall, 13.5% participating centres administered fatty stimuli that fell below the recommended 10 g. Widespread variations were found in GBEF normal ranges and fatty stimulus administration. Motion correction has a large effect on GBEF; in one data set, motion correction alone changed GBEF from 44 to 9%, but 25% of the participants stated motion correction was not used. Conclusion: The authors proposed gold standard is fat content of the stimulus should be at least 10 g; and images should be acquired for 60 min after stimulus. If GBEF is quoted, motion correction should be used, and if compared with a normal range, the stimulus used must fit with the reference.